Do Resource-Rich Countries Suffer from a Lack of Fiscal Discipline? - Bleaney, Michael; Halland, Havard (World Bank, Washington, DC, 2016)
Fiscal indicators for resource-rich and resource-poor low- and middle-income countries are compared using annual data from 1996 to 2012. Resource richness is defined by export composition: fuel greater than a 25 percent share and/or ores and metals greater than a 10 percent share. Fuel exporters have a significantly better general government fiscal balance than the rest of the sample, and higher revenues and expenditures, which are approximately evenly split between extra consumption expenditure and extra capital expenditure. Only about a quarter of their extra revenue goes into extra consumption expenditure, and this proportion has been lower since 2005. Fuel exporters' expenditure reacts with a lag to oil price fluctuations. There are no significant differences between ores and metals exporters and resource-poor countries, or between new and old resource exporters, in aggregate expenditures and revenues. Ores and metals exporters spend more on investment and less on government consumption. Some individual country cases are briefly discussed.